PERAN PUBLIC RELATIONS TELKOMSEL SEMARANG DALAM MEMBANGUN CITRA POSITIF DI MATA MASYARAKAT - Prasetyantono, Anggito; Suryanto, Suryanto (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2025)
Telkomsel is one of the largest cellular telecommunications operators in Indonesia and the first GSM operator in the country to launch postpaid services via Kartu HALO. The company offers three main GSM products: SimPATI (prepaid), Kartu AS (prepaid), and Kartu HALO (postpaid). Additionally, it provides wireless internet services through Telkomsel Flash. For over 15 years, Telkomsel has remained the market leader, supported by its slogan 'Begitu Dekat, Begitu Nyata,' which reflects its commitment to being close to customers through tangible services. To maintain its market leadership and a positive brand image, Telkomsel proactively defines its identity through strategic media relations. These initiatives include press conferences, press briefings, and special events involving both mass and social media. Furthermore, they regularly issue press releases to ensure consistent information flow. These routine activities are instrumental in fostering a positive public perception of the company."